Fingerprinting and molecular comparison among two parental strains of Trichoderma spp. and their corresponding fusants produced by protoplast fusion - Hardik N. Lakhani; Dinesh N. Vakharia; Mohamed M. Hassan; Ragaa A. Eissa (Biotechnology & Biotechnological Equipment, 2016)
Protoplast fusions are important tools in strain improvement for bringing genetic recombination and developing hybrid strains in filamentous fungi. These are the powerful techniques for engineering of microbial strains with desirable different properties. The molecular characterization of two parent's strains (Trichoderma harzianum NBAII Th 1, Trichoderma viride NBAII Tv 23) and their corresponding fusants, produced by protoplast fusion, was investigated by random amplified polymorphic DNA (RAPD), ISSR (inter-simple sequence repeats) and internal transcribed spacer (ITS) markers. Specific results for fingerprinting were obtained by the 20 primers of each RAPD and ISSR, and four primers of ITS, respectively. These markers produced different fragment patterns with varied number of bands and yielded a total of 419 distinct bands. 13.3% were considered as polymorphic bands and 86.7% were considered as monomorphic bands. For RAPD marker, the OPC-04 primer has showed the highest polymorphism, 58.3%. While in ISSR marker, the UBC-835 primer has showed the highest polymorphism, 57.2%. The dendrogram based on RAPD marker results grouped the two parent's strains and 21 fusants into two different clusters with about 97% genetic similarity. While the dendrogram based on ISSR and ITS markers results grouped the two parent's strains and 21 fusants into two different clusters with about 88% genetic similarity. Moreover, the smallest genetic distance (0.01) was estimated between fusant-10 and fusant-12; moreover, fusant-8 and fusant-20 relatively have the highest genetic distance. Our results are consistent with the conclusion that understanding the genetic variation within parent Trichoderma strains and their corresponding fusants and molecular occurrence of protoplast fusion using RAPD, ISSR and ITS markers.